2007
DOI: 10.1212/01.wnl.0000260695.72980.b7
|View full text |Cite
|
Sign up to set email alerts
|

A population-based survey of multiple sclerosis in Shanghai, China

Abstract: Multiple sclerosis prevalence in Shanghai is in line with that reported for other Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 17 publications
5
48
2
Order By: Relevance
“…Thus, the logical inference would be that a real rise of MS incidence has occurred in Tehran in the last two decades. Our prevalence found of 55.98/100,000 was lower than the figures of Greece and Turkey [10,24] but higher than in Kuwaitis, Jordanians and Chinese [8,11,25] . However, due to different inclusion criteria and variety in study methodology, a comparison of the results with these countries should be made with caution.…”
Section: Discussioncontrasting
confidence: 67%
“…Thus, the logical inference would be that a real rise of MS incidence has occurred in Tehran in the last two decades. Our prevalence found of 55.98/100,000 was lower than the figures of Greece and Turkey [10,24] but higher than in Kuwaitis, Jordanians and Chinese [8,11,25] . However, due to different inclusion criteria and variety in study methodology, a comparison of the results with these countries should be made with caution.…”
Section: Discussioncontrasting
confidence: 67%
“…Table 5 shows the epidemiological studies of MS in Asia after the year 2000 ranked by prevalence. The prevalence of MS in Taiwan is lower than that of most Asian countries except China Shanghai [25] . An increase in prevalence with time is not only observed in Taiwan, but also in other Asian countries, including Japan, Hong Kong, Kuwait and Jordan [17,18,[26][27][28][29][30][31][32][33][34] .…”
Section: Creutzfeldt-jakob Diseasementioning
confidence: 81%
“…In Japan, certain explanations for a decline in the mean age include more frequent utilization of MRI imaging as well as improved neurological care [17] . China Cheng et al [33] reported the MS prevalence of 1.39 per 100,000 (95% CI 1.16-1.66) in Shanghai. All studies used McDonald's criteria as diagnostic criteria among MS patients.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…All studies used McDonald's criteria as diagnostic criteria among MS patients. In our reviewed studies, MS prevalence is more common among females in comparison to males [30][31][32][33]35] . In the last 2 decades, the mean age at disease onset ranged from 46.4 in 1993 to 32.6 in 2006 [31,32] .…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%